Succession planning tool kit for academia administrators / Mohamed Fajil Abd. Batau ... [et al.] - Abd. Batau, Mohamed Fajil; Pakeer Mohamed, Ahmad Shah; Azlan, Ariff Aizuddin; Ismail, Mohd Faiz; Hassan Basri, Kamarul Aini (2021)
This succession planning kit is to identify and select high-potential administrators in academic institutions. Academic institutions mainly at the faculty level will engage in the managerial activities as dean, deputy dean, program coordinators, and other academic coordinators which are critical management positions. This kit will assist the academic institutions mainly faculty to identify potential leaders to groom leadership training development opportunities and selecting the right person for the right academic positions. This kit comes with three steps in selecting the potential academic administrators. The first step is talent pool applicant profile, the second step is management nomination and the third step is the selection process. The benefits are it could assist and guide in the decision- making process by academic institutions leaders, to identify the potential academic administrators for the academic institution's survival and choosing the right academic staff for the right position.